The Feasibility of Using a Portable Xenon Delivery Device to Permit Earlier Xenon Ventilation with Therapeutic Cooling of Neonates During Ambulance Retrieval. (June 2015) - Dingley, John; Liu, Xun; Gill, Hannah; Smit, Elisa; Sabir, Hemmen; Tooley, James; Chakkarapani, Ela; Windsor, David; Thoresen, Marianne
Abstract : BACKGROUND: Therapeutic hypothermia is the standard of care after perinatal asphyxia. Preclinical studies show 50% xenon improves outcome, if started early. METHODS: During a 32-patient study randomized between hypothermia only and hypothermia with xenon, 5 neonates were given xenon during retrieval using a closed-circuit incubator-mounted system. RESULTS: Without xenon availability during retrieval, 50% of eligible infants exceeded the 5-hour treatment window. With the transportable system, 100% were recruited. Xenon delivery lasted 55 to 120 minutes, using 174 mL/h (117.5–193.2) (median [interquartile range]), after circuit priming (1300 mL). CONCLUSIONS: Xenon delivery during ambulance retrieval was feasible, reduced starting delays, and used very little gas. Abstract : Published ahead of print March 19, 2015